KOMPETISI DAN STABILITAS PERBANKAN DI INDONESIA Suatu Pendekatan Analisis Panel Vector Autoregression - Apriadi, Intan; Sembel, Roy; Santosa, Perdana Wahyu; Firdaus, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
Banking fragility phenomenonÃ‚Â in the world as well as in Indonesia whip out some interesting issues to be investigated. The objective of this study is to investigate the dynamic causality relationship between competitionand stability of bank in Indonesia. The relationship between competition and stability of bank has long been a controversy before some crises takes place in the world either in theoretical or in empirical sphere. The crucial questionÃ‚Â such as will competitionÃ‚Â increase stability of banking industryÃ‚Â or the other way around will competition create instability in banking system in Indonesiaare going to be investigated in this study. Stability will be analyzed by z-score, and competition will be measured by HHI. Testing the relationship between competition and stability will be conducted by Panel Vector Autoregression, a relatively new approach in econometrics. Empirical result indicates that competition Ã‚Â decreasedstability of banking industry,whereas stability has aninsignificant effect to competition.